PENGEMBANGAN BUKU SAKU BERBASIS CERITA BERGAMBAR (KOMIK) PADA MATERI FLUIDA STATIS UNTUK KELAS XI SMA/MA - Muskholifah, Muskholifah; Partono, Partono; Riswanto, Riswanto (Universitas Muhammadiyah Metro, 2021)
Abstract: Research and development (Reseacrh and Development) of Learning Media for Book Based on Storytelling Pictures (Comics) Has been done on Static Fluids. The subjects of the study were 20 students of class XIMA NurulQodiri in the academic year 2018/2019. The development model used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The instruments used in the study were expert validation sheets, student response questionnaires and teacher response questionnaires. Based on the results of the study it was found that the percentage of scores from experts for the material component is 85.40% and graphics which is 78.43% each located in very decent criteria. While the response of students is 86.00% and the response of teachers by 87.78% obtained through product trials is in very good criteria. So it is seen from the average of the instruments developed 84.40% of the results it can be concluded that the Learning Media Based on Story-Based Pocket Books (comics) in the Static Fluorescent Material can be used in the study of Physics in SMA.Keywords: Development, Pocket Books, Teaching Materials, Picture Stories, Comics.